Pengaruh Investasi Pertambangan dan Tenaga Kerja terhadap Produk Domestik Regional Bruto serta Indeks Pembangunan Manusia di Kabupaten Kutai Barat - Yakin Masiku; Eny Rochaida; Adi Wijaya (Faculty of Economics and Business Mulawarman University, 2017)
In accordance with the Regional Autonomy Policy, the Regional Government will not be able to perform its functions properly, effectively and efficiently without adequate funding support to provide services to the community and implement development programs. The financing of development in the area other than sourced from the government itself also exists that comes from the private sector through Domestic Investment with Mining Investment which is certainly enough to contribute in the formation of Gross Regional Domestic Product and Human Development Index in West Kutai Regency. So the role of mining investment is very large in order to support and optimize the success of development in the region. Therefore developing and optimizing Investment Cultivation becomes very important, in an effort to increase the growth of GDP and future HDI. The purpose of this study was to examine the influence of investment and labor on Gross Regional Domestic Product and Human Development Index in West Kutai District. Data used secondary data sourced from the Mining Service of West Kutai Regency and Central Bureau of Statistics Office of West Kutai Regency, Bappeda of West Kutai Regency and related Office.The method of data collection with direct observation. Further data is processed and analyzed by Path Analysis (Path Analysis). The result of statistical test shows that partially Mining Investment has positive but not significant effect to PDRB and HDI, whereas the amount of Labor has positive and significant effect to the increasing of PDRB revenue in West Kutai Regency. While PDRB has a positive and significant impact on HDI in West Kutai Regency.Keywords: Human Development Index, Gross Regional DomesticProduct, Manpower, Mining Investment